1984
DOI: 10.1021/ja00317a064
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed, potent competitive inhibitors of leukotriene biosynthesis

Abstract: Several of the members of the series are good candidates for in vivo inhibition of leukotriene biosynthesis, including the sulfoxide, sulfone, and amide derivatives indicated. These compounds obviously are not susceptible to incorporation into phospholipid. Clearly, the RBL-1 5-lipoxygenase does not demand that the carboxyl surrogate be an anionic group.16 (15) The amide of 1 was prepared by ammonolysis of the methyl ester; all other carboxyl replacement analogues were synthesized from bromoacetylene 10 (undeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

1984
1984
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 1 publication
(1 reference statement)
0
39
0
3
Order By: Relevance
“…There is chemical and computational evidence indicating that arachidonic acid, the parent fatty acid of anandamide, favors a bent or looped conformation in which the carbonyl group is proximal to the C14-C15 olefinic bond. The chemical evidence for such a conformation includes the highly regiospecific intramolecular epoxidation of arachidonyl peracid [103] and the facile macrolactonization of the C20 hydroxyl methyl arachidonate [104]. These experimental results are corroborated by molecular dynamics calculations [105] which indicate that indeed a bent conformation is thermodynamically favorable.…”
Section: ) Tail N-pentyl Group Modificationsmentioning
confidence: 85%
“…There is chemical and computational evidence indicating that arachidonic acid, the parent fatty acid of anandamide, favors a bent or looped conformation in which the carbonyl group is proximal to the C14-C15 olefinic bond. The chemical evidence for such a conformation includes the highly regiospecific intramolecular epoxidation of arachidonyl peracid [103] and the facile macrolactonization of the C20 hydroxyl methyl arachidonate [104]. These experimental results are corroborated by molecular dynamics calculations [105] which indicate that indeed a bent conformation is thermodynamically favorable.…”
Section: ) Tail N-pentyl Group Modificationsmentioning
confidence: 85%
“…Nalkyl derivatives of arachidonohydroxamic acid 34 [46] were the first compounds prepared. Although the skeleton of these compounds was modified 35-38, biological half-time prolongation was not achieved and their R&D was terminated.…”
Section: Iron Chelating Compoundsmentioning
confidence: 99%
“…The first validation of this hypothesis was the synthesis of arachidonohydroxamic acid as a potent in vitro inhibitor of 5-LO. 17 Low molecular weight, non-lipid hydroxamates were subsequently identified that were also potent in vitro inhibitors. This strategy of inhibitor design was elaborated using various 5-substituted-6,8,11,14-eicosatetraenoic acid (5-HETE) analogs 18,19 and 15-HETE templates.…”
Section: -Lipoxygenase Inhibitors That Have Progressed To Clinical Ementioning
confidence: 99%